Internalisasi Nilai-Nilai Moderasi Beragama Melalui Layanan Khusus dan Program Pendidikan untuk Peserta Didik di Sekolah Alam Saka Kediri - Rahma, Lailatul (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research explores the process of internalizing the values of religious moderation through special services and educational programs for students at Sekolah Alam SAKA Kediri. The research method uses a qualitative approach with data collection techniques through observation, interviews, and analysis of related documents. The research focuses on the process of implementing special service programs. The research results show that the Sekolah Alam SAKA Kediri has developed a unique service program for students to actively understand and practice the values of religious moderation through special services such as laboratory services, catering, UKS, and library. Apart from developing students' talents and interests, the educational program also focuses on opportunities to discover new experiences and environments, such as entrepreneurship-based programs, namely SAKA Business Day and Shopping Day. Meanwhile, to support students in developing communication and social skills by involving students as zakat recipients and carrying out internship activities. Apart from that, focusing on the morning activity program and the concept of talent-friendly and inclusive education also positively impacts creating a school environment that is responsive and anti-bullying.